Depth Map Super-Resolution via Cascaded Transformers Guidance - Ariav, Ido; Cohen, Israel (Frontiers in Signal Processing, 2022)
Depth information captured by affordable depth sensors is characterized by low spatial resolution, which limits potential applications. Several methods have recently been proposed for guided super-resolution of depth maps using convolutional neural networks to overcome this limitation. In a guided super-resolution scheme, high-resolution depth maps are inferred from low-resolution ones with the additional guidance of a corresponding high-resolution intensity image. However, these methods are still prone to texture copying issues due to improper guidance by the intensity image. We propose a multi-scale residual deep network for depth map super-resolution. A cascaded transformer module incorporates high-resolution structural information from the intensity image into the depth upsampling process. The proposed cascaded transformer module achieves linear complexity in image resolution, making it applicable to high-resolution images. Extensive experiments demonstrate that the proposed method outperforms state-of-the-art techniques for guided depth super-resolution.